Effect Of Application Of Mineral Trioide Aggregate (Mta) And Nanohydroxyapatite In Duck Egg Shell On Macrophages In Reversible Pulpitis - Shinta Marliana; Cahyani Cahyani; Ikmal Hafizi; Nur Ariska Nugrahani (Jurnal EduHealth, 2023)
Pulp disease is caused by bacteria that cause tooth decay in the form of caries. These bacteria can penetrate the pulp through the gaps in the dentine, and develop in the dentinal tubules so that the permeability of the dentinal tubules decreases. Reversible pulpitis is a type of pulp disease, which if left untreated will develop into irreversible pulpitis. Pulp capping treatment as a treatment for non medicament aims to maintain the pulp to remain vital by reducing the inflammatory process. Macrophages as a marker that can be used as a sign when inflammation occurs. Pulp capping treatment usually use calcium hydroxide and Mineral Trioxide Aggregate (MTA) as material agent. Duck egg shells contain calcium carbonate and Mineral Trioxide Aggregate has an effectiveness over calcium hydroxide. the purpose of this study is to determine the difference in the number of macrophages in reversible pulpitis using duck egg nanohydroxyapatite (NHA) and MTA. this research is an in vivo laboratory experimental post test only control design with 27 research samples which one control group and two experiment group. The independent variables are duck egg nanohydroxyapatite and MTA, and the dependent variable is differences in the number of macrophages. there were significant differences in the three groups, where the average value of macrophage formation was lowest in the group of rats that were applied to MTA and followed by the NHA group. Meanwhile, the control group, the reversible pulpitis rat group without medicament application, had the highest average score. The application of MTA as a pulp capping medicament can reduce macrophages in reversible pulpitis using rats Sprague Dawley.